Propagation and Cultivation Protocols for Wild Creeping Bellflowers (Campanula rapunculoides L.) - SCARIOT, VALENTINA; GAINO, Walter; DEVECCHI, Marco (2012)
Few European native plants have been considered by rigorous improvement programs. Basically these species are still wild plants seeding spontaneously and their cultivation requirements are rather unknown. C. rapunculoides L. is a perennial plant with attractive blue bell-shaped flowers, growing in stony and woodland areas of Europe, except in arctic regions and islands. With the final purpose of offering and introducing a sufficient number of vigorous plants with the same characteristics to the flower market, the assessment of its propagation and cultivation protocols is required. An appropriate species should also be characterized by an extended flowering season or at least dispose of several cultivars with slightly overlapping flowering periods. Campanulas flower mostly in late spring or early summer and have a relatively short flowering season. Little is known about what triggers flowering. Its manipulation, e.g. the possibility to make the plants flower on demand, would be beneficial. The present research investigated the propagation attitude by cutting and division of wild specimens of C. rapunculoides. Plants grown in greenhouse primarily and later distributed to several commercial greenhouses where they cultivated under different conditions (pot/soil, greenhouse/open air). Plant growth, health, vigour and shape and bloom characteristics were observed. Effects of substrate amendments, pruning techniques and vernalisation on flower characteristics and yield were also evaluated in two different populations. Differences were detected according to both culture conditions/practices and population origin. Growers can adapt this information in order their cultivation meets market needs.